2020
DOI: 10.5483/bmbrep.2020.53.8.087
|View full text |Cite
|
Sign up to set email alerts
|

Emerging functions for ANKHD1 in cancer-related signaling pathways and cellular processes

Abstract: ANKHD1 (ankyrin repeat and KH domain containing 1) is a large protein characterized by the presence of multiple ankyrin repeats and a K-homology domain. Ankyrin repeat domains consist of widely existing protein motifs in nature, they mediate protein-protein interactions and regulate fundamental biological processes, while the KH domain binds to RNA or ssDNA and is associated with transcriptional and translational regulation. In recent years, studies containing relevant information on ANKHD1 in cancer biology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…YAP1, SIVA, SHP2, p21, SMYD3, and STAT3 interact with ANKHD1 in different cancer contexts (Almeida & Machado‐Neto, 2020); therefore, we also characterized their expression in our cell line panel to shed light on possible interactions mediated by ANKHD1 in this neoplasia. Although discrepancies between the mRNA and protein expression for some of the targets analyzed here (Figure 1c), and may be due to posttranslational regulation, two important patterns were observed for the breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…YAP1, SIVA, SHP2, p21, SMYD3, and STAT3 interact with ANKHD1 in different cancer contexts (Almeida & Machado‐Neto, 2020); therefore, we also characterized their expression in our cell line panel to shed light on possible interactions mediated by ANKHD1 in this neoplasia. Although discrepancies between the mRNA and protein expression for some of the targets analyzed here (Figure 1c), and may be due to posttranslational regulation, two important patterns were observed for the breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Ankyrin repeat and KH domain‐containing protein 1 (ANKHD1) has been identified as a regulator of important signaling pathways and cellular processes with relevance in cancer (Almeida & Machado‐Neto, 2020). ANKHD1 is known to contribute to the proliferation, migration, and invasion of different neoplastic cells in vitro (Fragiadaki & Zeidler, 2018; Machado‐Neto et al, 2015) and tumorigenesis in vivo (Liu et al, 2020; Machado‐Neto et al, 2014; Yao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANKHD1 (ankyrin repeat and K‐homology domain containing 1) is a large protein characterized by the presence of a K‐homology domain, which could bind to RNA or ssDNA, and is found in proteins associated with transcriptional and translational regulation [ 40 , 41 ]. ANKHD1 were widely expressed in normal tissues and cancer cell lines at different levels, and the aberrant expression of ANKHD1 has been reported in some types of cancer [ 42 ]. Previous studies had shown the evidence of ANKHD1 in the malignant phenotype of cancer cells, including promoting cancer cell proliferation, migration, invasion, and tumorigenesis [ 42 ], by positively regulating of YAP1 [ 43 , 44 ], JAK/STAT [ 45 ], and STMN1 [ 46 , 47 ], and negatively regulating p21 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANKHD1 were widely expressed in normal tissues and cancer cell lines at different levels, and the aberrant expression of ANKHD1 has been reported in some types of cancer [ 42 ]. Previous studies had shown the evidence of ANKHD1 in the malignant phenotype of cancer cells, including promoting cancer cell proliferation, migration, invasion, and tumorigenesis [ 42 ], by positively regulating of YAP1 [ 43 , 44 ], JAK/STAT [ 45 ], and STMN1 [ 46 , 47 ], and negatively regulating p21 [ 48 ]. In our study, we demonstrated that PTEN could induce p21 expression via interacting with ANKHD1 and enhancing the binding degree of ANKHD1 to the p21 promoter in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%